Poverty alleviation through e-commerce: Village involvement and demonstration policies in rural China - Chao PENG; Biao MA; Chen ZHANG (Journal of Integrative Agriculture)
The diffusion of e-commerce has played a significant role in recent rural economic development in China. E-commerce is also considered as an efficient channel to alleviate poverty in rural China. Voluminous studies have investigated the contribution of e-commerce to agricultural development, yet it is lacking empirical evidence as to the effects of e-commerce on rural poverty alleviation. Since the year of 2014, in order to develop rural e-commerce, Chinese government launched the National Rural E-commerce Comprehensive Demonstration Project. This gradual involvement policy offered a natural experiment for evaluation of e-commerce. Based on village-level survey data from rural China and Heckit method, our study finds that rural e-commerce has a significantly positive effect on rural income. Moreover, the effect is inverted U-shaped for the relative-poverty villages. The estimation of the propensity scores matching model confirms that the results are robust. The following policy recommendations are proposed: (1) policy support to rural e-commerce should prioritize the poverty-stricken villages. By doing so, the marginal income effects of e-commerce will be maximized. (2) Investment in internet infrastructure and establishment of human resources for e-commerce in rural areas will have spillover effects, increasing rural income through the “digital dividend”.